GENETIC DIVERGENCE AND HETEROSIS AMONG MAIZE GENOTYPES AS INFERRED FROM DNA MICROSATELLITES - NIHARIKA SHUK LA; D. K. MISHRA; ARUN CHAVAN; SANJAY SINGH (The Bioscan, 2014)
This study was under taken to investigate the genetic diversity among germplasm of maize and to screen out diversified parent to develop hybrids with high yield potential. Simple sequence repeat (SSR) analysis of 29 markers was performed for 88 germplasm comprising of CIMMYT based QPM lines and desimaize collected from tribal areas of Madhya Pradesh.An average of 3.10 alleles per locus was observed with a range from 2 to 5. The polymorphic information content (PIC) of the 29 SSRs ranged from, 0.11 to 0.62 with an average of 0.36. The clustered dendrogram classified the germplasm into two groups that could easily facilitate the selection of diversified parents. Total 11 hybrids, whose parents were diverse, were reported with higher percentage of heterotic effect for yield attributing traits, which may be used as inbreds for obtaining higher yield potential. However results of genotyping of maize inbreds with SSR markers established a benchmark on the genetic diversity existing across the inbreds and hence these DNA marker profiles can be used as criteria for the prediction of heterosis in maize and also for hybrid identification.